The relationship of interest rate among Asian countries to the Malaysia Interest rate / Nur Syafirah Mohd Zuki - Mohd Zuki, Nur Syafirah (Faculty of Business and Management, 2017)
The aim of this study is to investigate the relationship of interest rate among Asian countries to the Malaysia interest rate. The study used Simple Linear Regression and Multiple Linear Regression in order to find the relationship among independent variables and dependent variable. The data is collected from year 2005 until 2016 and conduct in quarterly basis. From the result, it reveals that Japan interest rate have an insignificant relationship toward Malaysia interest rate. However, South Korea interest rate and Singapore interest rate have significant relationship toward Malaysia interest rate. These results give additional understanding of the relationship interest rate between the Asian countries and should be useful for regulator, investor and speculator.